β-Glucosidase VmGlu1 is required for toxin production and pathogenicity of Valsa mali - Xinyue Cui; Dewan Zhang; Liyong Gao; Na Liu; Sen Lian; Weichao Ren; Baohua Li; Caixia Wang (Phytopathology Research)
Abstract Flavonoids, serving as crucial secondary metabolites, are widely distributed in plants and play a key role in inhibiting microbial growth, protecting plants from pathogen invasion, and conserving energy. Our previous study revealed that the β-glucosidase VmGlu2 effectively catalyzes the degradation of phloridzin, a typical flavonoid in apples, and regulates the pathogenic process of Valsa mali. However, VmGlu2 exhibits a lower efficiency in degrading rutin, another characteristic flavonoid in apples. In this study, we found that the expression level of the β-glucosidase gene VmGlu1 was induced by 9.42-fold following rutin treatment, and VmGlu1 possessed the capability to degrade both rutin and phloridzin, but under the same conditions, VmGlu1 showed a distinct preference for rutin degradation, with an initial degradation rate 8.66 times higher than that of VmGlu2. Targeted deletion of VmGlu1 resulted in a 99.32% reduction in pycnidia production, a nearly 33% decrease in toxin production, and a significant decrease in pathogenicity on apple twigs and leaves. Furthermore, we verified that VmGlu1 and VmGlu2 exhibit functional redundancy in pycnidia production, toxin-related β-glucosidase activity, and pathogenicity by generating double-deletion mutants. The results of this study provide valuable insights into the roles of VmGlus in the interaction of V. mali and apple during the infection process.